2020
DOI: 10.18026/cbayarsos.629328
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de İntihar Üzerinde Etkili Olan Sosyoekonomik Faktörler: Ekonometrik Bir Analiz

Abstract: Although it is generally accepted that the cultures, religious beliefs, traditions, welfare levels and social structures of the countries may have an impact on suicidal tendencies, the increasing number of suicide cases worldwide and the epidemiological structure of suicide phenomenon reveals the necessity to accept suicide as a public health problem and importance of determining the factors leading to suicide in terms of finding urgent and effective solutions. The aim of this study was to investigate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
1
1
1
Order By: Relevance
“…Our result obtained from model 2 also does not coincide with the panel data study of Fountoulakis et al (2014), which found a negative relationship between suicide and inflation. In model 2, contrary to Varol and Karagöz (2020), we found that inflation has a statistically significant and positive impact on suicide. The Turkish economy has suffered from a long-run inflation problem since the 1970s.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Our result obtained from model 2 also does not coincide with the panel data study of Fountoulakis et al (2014), which found a negative relationship between suicide and inflation. In model 2, contrary to Varol and Karagöz (2020), we found that inflation has a statistically significant and positive impact on suicide. The Turkish economy has suffered from a long-run inflation problem since the 1970s.…”
Section: Discussioncontrasting
confidence: 86%
“…Recent studies have examined unemployment, GDP, suicide association (Altinanahtar and Halicioglu, 2009), inflation and suicide relationship (Varol and Karago ¨z, 2020) and suicide dynamics (Akyuz et al, 2020) for Turkey. Few concerns were allocated to the impact of economic factors, except for unemployment and GDP, on suicide in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…108 Çakar, 487. 109 Açıkgöz,24,83,87,100,101,119,132,159,[193][194][195][196]203. 110 Hüseyin Kutlu, Kaybolan Medeniyetimiz Hekimoğlu Ali Paşa Camii Haziresindeki Tarihi Mezar Taşları, Damla Yayın Evi, İstanbul 2005, 141-154-155-158-159-171. sarıklı kavuk) 141 , Tarsus Arkeoloji Müzesi'ndeki Osmanlı Dönemi mezar taşları 1 (çubuklu başlıklı taşkın sarıklı kavuk) 142 , Geç Dönem Osmanlı Adana mezar taşlarında 3 (2'si çubuklu başlıklı taşkın sarıklı, 1'i çubuklu başlıklı kısa sarıklı kavuk) 143 , Tokat'ta 3 144 Uşak'ta Osmanlı mezar taşlarında 145 , Manisa Gördes'te 4 (3'ü çubuklu başlıklı taşkın sarıklı, 1'i çubuklu başlıklı uzun sarıklı kavuk) 146 ve Kosava Mehmet Paşa Camii Haziresi'nde 4 (çubuklu başlıklı taşkın sarıklı kavuk) 147 , Yunanistan İskece Çınar Camii Haziresi'nde 1, Yeni Camii Haziresi'nde 2 148 örnekleri tespit edilmiştir (Grafik 4).…”
Section: Grafik 1: Selimi Kavuk Dağılımıunclassified